A system for real‐time monitoring of breath‐hold via assessment of internal anatomy in tangential breast radiotherapy. Issue 1 (18th November 2021) - Vasina, Elena N.; Greer, Peter; Thwaites, David; Kron, Tomas; Lehmann, Joerg
Abstract: The deep inspiration breath‐hold (DIBH) technique assists in sparing the heart, lungs, and liver during breast radiotherapy (RT). The quality of DIBH is currently assessed via surrogates which correlate to varying degrees with the patient's internal anatomy. Since modern linacs are equipped with an electronic portal imaging device (EPID), images of the irradiated anatomy streamed from EPIDs and analyzed in real time could significantly improve assessment of the quality of DIBH. A system has been developed to quantify the quality of DIBH during tangential breast RT by analyzing the "beam's eye view" images of the treatment fields. The system measures the lung depth (LD) and the distance from the breast surface to the posterior tangential radiation field edge (skin distance, SD) at three user‐defined locations. LD and SD measured in real time in EPID images of two RT phantoms showing different geometrical characteristics of their chest wall regions (computed tomography dose index [CTDI] and "END‐TO‐END" stereotactic body radiation therapy [E2E SBRT]) were compared with ground truth displacements provided by a precision motion platform. Performance of the new system was evaluated via static and dynamic (sine wave motion) measurements of LD and SD, covering clinical situations with stable and unstable breath‐hold. The accuracy and precision of the system were calculated as the mean and standard deviation of the differences between the ground truth and measured values. The accuracy of the static measurements of LD and SD for the CTDI phantom was 0.31 (1.09) mm [mean (standard deviation)] and –0.10 (0.14) mm, respectively. The accuracy of the static measurements for E2E SBRT phantom was 0.01 (0.18) mm and 0.05 (0.08) mm. The accuracy of the dynamic LD and SD measurements for the CTDI phantom was –0.50 (1.18) mm and 0.01 (0.12) mm, respectively. The accuracy of the dynamic measurements for E2E SBRT phantom was –0.03 (0.19) mm and 0.01 (0.11) mm.